This is not my home - Yoh, Eugenia; Chang, Vivienne (Little, Brown and Company, 2023)
Lily is upset when her mother announces the family will be moving back to Taiwan to care for her Ah Ma, but when her mother explains Taiwan is her home, Lily agrees it is her home too.